Photometric changes on Saturn's Titan: Evidence for active cryovolcanism - Nelson, R; Kamp, L; Lopes, R; Matson, D; Kirk, R; Hapke, B; Wall, S; Boryta, MD; Leader, F; Smythe, W; Mitchell, K; Baines, K; et al. (2009)
We report infrared spectrophotometric variability on the surface of Saturn's moon Titan detected in images returned by the Visual and Infrared Mapping Spectrometer (VIMS) onboard the Cassini Saturn Orbiter. The changes were observed at 7°S, 138°W and occurred between October 27, 2005 and January 15, 2006. After that date the surface was unchanged until the most recent observation, March 18, 2006. We previously reported spectrophotometric variability at another location (26°S, 78°W). Cassini Synthetic Aperture RADAR (SAR) images find that the surface morphology at both locations is consistent with surface flows possibly resulting from cryovolcanic activity (Wall et al., companion paper, this issue). The VIMS-reported time variability and SAR morphology results suggest that Titan currently exhibits intermittent surface changes consistent with present ongoing surface processes. We suggest that these processes involve material from Titan's interior being extruded or effiised and deposited on the surface, as might be expected from cryovolcanism. © 2009.